2016
DOI: 10.1080/03323315.2016.1146156
|View full text |Cite
|
Sign up to set email alerts
|

The degree to which students and teachers are involved in second-level school processes and participation in decision-making: an Irish Case Study

Abstract: The Education Act (1998) is a key policy document in Irish education, emphasising the rights, roles and responsibilities of key stakeholders, including parents, teachers and pupils in schools. Since 1998 the Department of Education and Skills (DES) has stressed the need to introduce an increased role for teachers and pupils in decision-making. It is therefore timely to explore the response of teachers and students to such a collaborative school environment in a rural second-level school of approximately 600 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In order to refract the current situation, the state educational policy set the course for the inclusion of parents in school education innovative development. This trend of key participant involvement in innovation management is characteristic of modern developed countries [8]. However, according to the results of the study, there is a consistently low participation of parents in this process -less than one third of schoolchildren parents (Diagram 2).…”
Section: Diagram 1 the Assessment Of Educational Innovation Implementmentioning
confidence: 80%
See 1 more Smart Citation
“…In order to refract the current situation, the state educational policy set the course for the inclusion of parents in school education innovative development. This trend of key participant involvement in innovation management is characteristic of modern developed countries [8]. However, according to the results of the study, there is a consistently low participation of parents in this process -less than one third of schoolchildren parents (Diagram 2).…”
Section: Diagram 1 the Assessment Of Educational Innovation Implementmentioning
confidence: 80%
“…This setting is traced in the studies that justify the need for a more active role of key participants in the decision-making process [8]. It is concluded that feedback is important not only for trivial issues, but also for the development of the educational system as a whole, including the content and the trend of innovative educational projects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Survey data examined by de Róiste et al (2012) indicate that most students are encouraged to express their views in class, but with opportunities decreasing as students move through the school system. There has been an increase in recent years in research reporting that there is a desire among students in Irish post-primary schools for discussions, opinion sharing, and more of a say in their lessons (Smyth, Banks, and Calvert 2011;Smyth and Banks 2012;Harrison, McNamara, and O'Hara 2020), and while this is happening to an extent, are classroom-level consultations still infrequent? Fleming's (2013) doctoral research shows how uncommon and alien student voice in Irish post-primary classrooms can be, while Harrison et al's (2020) case study research in one post-primary school found that most students felt they were 'rarely' involved in decision-making at the classroom level.…”
Section: Are Classroom-level Consultations Infrequent?mentioning
confidence: 99%
“…In Ireland, as elsewhere, the concept of student voice has become much stronger in official discourse in recent years. There has been an increase in research reporting that there is a desire among students in Irish post-primary schools for discussions, opinion sharing, and more of a say in their lessons (Smyth, Banks, and Calvert 2011;Smyth and Banks 2012;Harrison, McNamara, and O'Hara 2020) but in practice it appears that the traditional pedagogy of teaching in Ireland consisting of more teacher-centred approaches with little input from students continues to prevail to a large degree. As the following comments from teachers in Fleming's (2013, 164-165) doctoral research show, consulting students on classroom practice can be daunting for teachers in Irish postprimary schools, as well as being unique for all involved parties:…”
Section: Student Voice and Classroom Practicementioning
confidence: 99%